1960
DOI: 10.1002/j.1537-2197.1960.tb10622.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gibberellic Acid on Stem Apices of Vernalizable Grasses

Abstract: Koller, D. (Hebrew U., Jerusalem, Israel), H. R. Highkin, and O. H. Caso. Effects of gibberellic acid on stem apices of vernalizable grasses. Amer. Jour. Bot. 47(6) : 518–524. Illus. 1960.—Gibberellic acid was found to have distinct morphogenic effects on the stem apices of 3 vernalizable but unvernalized grasses: Hordeum vulgare var. ‘Kentucky,’ Hordeum bulbosum and Secale cereale var. ‘Winter Petkus.’ In these 3 species, GA caused the activation of lateral meristems on the embryonic nodes of the stem apices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…[1][2][3][4][5][6]. Our interpretation is supported by the fact that GA3 treatment of sorghum induces not one but several characteristics of the floral condition in a manner similar to that documented for barley (12) where GA3 promotion of floral initiation is well known (3,7). These characteristics include: (a) both elongation and widening of the apical meristem, (b) the absence of tightly appressed leaf primordia covering the apical dome, (c) the eventual occurrence of blunt lobes rather than obvious leaf primordia on the flanks of the meristem, and (d) development of a constriction below the apical dome.…”
Section: Methodssupporting
confidence: 61%
“…[1][2][3][4][5][6]. Our interpretation is supported by the fact that GA3 treatment of sorghum induces not one but several characteristics of the floral condition in a manner similar to that documented for barley (12) where GA3 promotion of floral initiation is well known (3,7). These characteristics include: (a) both elongation and widening of the apical meristem, (b) the absence of tightly appressed leaf primordia covering the apical dome, (c) the eventual occurrence of blunt lobes rather than obvious leaf primordia on the flanks of the meristem, and (d) development of a constriction below the apical dome.…”
Section: Methodssupporting
confidence: 61%
“…We conclude that the Sirael variety does not require vernalization or a short-day photoperiod to transition to the generative stage. According to [57], despite the occurrence of flowering, it is concluded that the role of GA in this phenomenon is restricted to the activation of lateral meristems in the apex. Mironovskaya achieved head-emergence on average a week later than Bezostaya with the same vernalization period of eight weeks [58].…”
Section: Development Of the Growing Pointmentioning
confidence: 99%